Factors associated with gastrointestinal side effects after liraglutide treatment for type 2 diabetes - Wu, Hao; Lu, Zongshi; Chen, Runyao; Cai, Quanfang; Wang, Miaomiao; Zhang, Liting; Zhu, Zhiming (Frontiers in Endocrinology, 2023)
Aim To identify risk factors predictive or associated with gastrointestinal side effects (GISEs) of liraglutide in patients with type 2 diabetes (T2DM). Methods T2DM patients treated with liraglutide for the first time were obtained and grouped into patients without GISEs and patients with GISEs. Baseline variables, including age, sex, BMI, glycemia profiles, alanine aminotransferase, serum creatinine, thyroid hormones, oral hypoglycemic drugs and history of gastrointestinal diseases, were tested for possible associations with GISEs outcome. Significant variables were entered into univariate and multivariate logistic regression (forward LR) analyses. ROC curves to determine clinically useful cutoff values. Results A total of 254 patients (95 female) were included in this study. 74 cases (29.13%) reported GISEs and 11 cases (4.33%) discontinued treatment. The results of univariate analyses showed that sex, age, TSH, FT3, α-glucosidase inhibitor (AGI), and concomitant gastrointestinal diseases were associated with GISEs occurrence (all p <0.05). In the final regression model, AGI use (adjusted OR=3.98, 95%CI: 1.88-8.40, p<0.001), gastrointestinal diseases (adjusted OR=3.27, 95%CI: 1.50-7.13, p=0.003), TSH (adjusted OR=1.78, 95%CI: 1.27-2.50, p=0.001) and male (adjusted OR=0.20, 95%CI: 0.1-0.39, p<0.001) were independently associated with GISEs. Furthermore, ROC curve analysis confirmed that the values of TSH 1.33 and 2.30 in females and males, respectively, were useful thresholds for predicting GISEs. Conclusion This study suggests that the combination of AGI, concomitant gastrointestinal diseases, females and higher TSH levels are independent risk factors of GISEs of liraglutide treatment in patients with T2DM. Further research is warranted to elucidate these interactions.